Eye tracking as an objective measure of hyperphagia in children with Prader-Willi syndrome - Key, Alexandra P.; Zengin-Bolatkale, Hatun; Dimitropoulos, Anastasia; Doernberg, Ellen (Wiley, 2020)
This study examined sensitivity of eye tracking measures to hyperphagia severity in Prader-Willi syndrome (PWS). Gaze data were collected in 57 children with PWS, age 3-11 years, and 47 typically developing peers at two study sites during free visual exploration of complex stimulus arrays that included images of food, animals, and household objects. Analysis of the number and duration of fixations as well as gaze perseverations revealed that food items are not exceptionally salient for children with PWS. Instead, increased attention to food in the context of other high-interest items (e.g., animals) was associated with caregiver reports of more severe hyperphagia and more advanced nutritional phase. The study also provided preliminary evidence of possible genetic subtype and sex differences as well as demonstrated that multiple investigators in a wide range of settings can effectively implement the eye tracking protocol. The results indicate that gaze characteristics derived from eye tracking may be a promising objective marker of hyperphagia in PWS for use in research and clinical trials.
Keywords: Eye Tracking; Hyperphagia; Nutritional Phase; Prader-Willi Syndrome